دور مواقع التواصل الاجتماعي في تعزيز العمل التطوعي في ظل جائحة كورونا (الفيسبوك نموذجا) - باهي، سندس, حمودي، أسماء (جامعة الوادي university of Eloued, 2021)
الملخص: تناولت هذه الدراسة بالطرح و المناقشة موضوع: دور مواقع التواصل الإجتماعي –فيسبوك- في تعزيز العمل التطوعي في ظل جائحة كورونا،دراسة ميدانية على عينة جمعية دروب الخير ولاية الوادي. حيث هدفت هذه الدراسة إلى محاولة التعرف على الدور الحقيقي لمواقع التواصل الإجتماعي في ظل جائحة كورونا. و إبراز أهمية و دور الفيسبوك بإعتباره وسيلة العصر في تعزيز العمل التطوعي. - حيث إعتمدنا في دراستنا على المنهج الوصفي ، و ذلك بدراسة عينة عشوائية قصدية تمثلت في جمعية "دروب الخير" تنشط على مستوى ولاية الوادي ، و ذلك بواسطة إستخدام المقابلة و الإستبيان كأدوات لدراستنا، حيث قمنا بتوزيع 33 إستمارة على مفردات العينة المنخرطين في الجمعية. • و من أهم النتائج التي توصلنا إليها في هذه الدراسة: - أكدت نتائج دراستنا أن شبكات التواصل الإجتماعي ساهمت بدور كبير و فعال في تعزيز العمل التطوعي في ظل جائحة كورونا. - كما أكدت ان أغلبية المنظمين لعينة الدراسة "جمعية دروب الخير" يستخدمون مواقع التواصل الإجتماعي بدافع المساهمة في دعم الجمعية و التطوع فيها. - و أيضا أكدت بأن شبكات التواصل الإجتماعي –الفيسبوك- إحتلت الصدارة لشيوعه و إنتشاره المبهر أكثر من أي شبكة أخرى و إهتمامه بتعزيز و نشر ثقافة العمل التطوعي في ظل جائحة كورونا. Résumé : This study dealt with the presentation and discussion of the topic: The role of social networking sites - Facebook - in promoting volunteer work in light of the Corona pandemic، a field study on the sample of the Paths of Good Association in the state of Wadi. As this study aimed to try to identify the true role of social media in light of the Corona pandemic. And highlighting the importance and role of Facebook as it is a modern way of promoting volunteer work. - Where we relied in our study on the descriptive approach، by studying an intentionally random sample represented by the "Paths of Goodness" association operating at the level of the wilaya of the valley، by using the interview and questionnaire as tools for our study، as we distributed 33 forms on the vocabulary of the sample who were involved in the association. • And among the most important results that we reached in this study: - The results of our study confirmed that social networks have played a large and effective role in promoting volunteer work in light of the Corona pandemic. - She also confirmed that the majority of the organizers of the study sample "Paths of Goodness Association" use social networking sites for the motive of contributing to the association's support and volunteering with it. - And also I confirmed that social networks - Facebook - were at the forefront of its popularity and impressive spread more than any other network and its interest in promoting and spreading the culture of volunteering in light of the Corona pandemic.
دراسة ميدانية على الجمعية الخيرية "دروب الخير" ولاية الوادي
مذكرة ماستر علم الاجتماع تخصص علم إجتماع الاتصال
Keywords: مواقع التواصل الإجتماعي، العمل التطوعي، كورونا; Réseaux sociaux, bénévolat, Corona; Social media, volunteer work, Corona